New specimens of Yanornis indicate a piscivorous diet and modern alimentary canal. - Xiaoting Zheng (Public Library of Science (PLoS), 2014)
A crop adapted for an herbivorous diet of seeds has previously been documented in the Early Cretaceous birds Sapeornis and Hongshanornis. Here we report on several specimens of Yanornis that preserve a crop containing fish. One specimen preserves two whole fish in the oesophagus, indicating that Early Cretaceous birds shared trophic specializations with Neornithes for the increased energetic demands of flight--namely the storing of food for later consumption when the stomach is full. Whole fish also indicate that despite their presence, teeth were not used to orally process food, suggesting the hypertrophied dentition in this taxon were utilized in prey capture. The presence of macerated fish bones in the crop of other specimens indicates the highly efficient advanced muscular system of peristalsis responsible for moving ingested items between different segments of the alimentary canal was also in place. Despite the fact many features of the modern avian alimentary canal are inferred to compensate for the absence of teeth in birds (expandable oesophagus, grinding gizzard), the derived alimentary canal was apparently present in toothed Cretaceous birds. Although Yanornis was considered to have switched their diet from piscivorous to herbivorous, based on position and morphology we reinterpret the gastroliths reported in one specimen as sand impacted in the intestines, and reconstruct the taxon as primarily piscivorous. This is a novel interpretation for fossilized gastroliths, and the first documentation of this condition in the fossil record.